Islamic Solidarity Games (ISG): Historical perspective - Sofyan, Davi; Saputra, Yudha Munajat; Nurihsan, Juntika; Kusmaedi, Nurlan (UIR Press, 2021)
The beauty of philosophy and approach in Islam is that it wants to provide a dignified and decent life for all human beings regardless of their race, ethnic or their nationality. To uplift humanity and protect their honour, Islam introduces the concept of solidarity in jurisprudence and solidarity regulated in Islamic law. In order to strengthen solidarity in the field of sports, the Islamic Solidarity Sport Federation (ISSF) was formed to serve the needs of Muslims in sports. For the first time the biggest sporting event for Muslims was held outside the Middle East region, precisely in the city of Palembang, Indonesia. The Islamic Solidarity Games (ISG) event aims to strengthen relations for countries that are predominantly Muslim. This article aims to provide an overview of the implementation of the Islamic Solidarity Games 1st, 2nd, 4th, and especially in the 3rd edition in Palembang, Indonesia, covering the background, objectives, implementation, and real impact for the host of the event as well as the dynamics of the strength of the international sports system. This study uses a literature review to support the achievement of the objectives of writing this article. The findings from this literature study are that the ISG as a form of sport can be a solution behind the tensions between the Arabian Peninsula countries. ISG has the potential to become a new force in the international sports system